The determinants of household debt in Malaysia / Abu Nidal Johan Abd Aziz - Abd Aziz, Abu Nidal Johan (Faculty of Business and Management, 2019)
Household debt is the one of the important matters that need to be look seriously and done carefully. An error happen in managing household debt can lead to financial distress and bankruptcy. The aim of this study is to determine the factors of influencing rising in household debt in Malaysia between the variables which is population growth, interest rate, inflation rate, housing price index and household income. This study is using time series data for the period of thirty years starting from year 1987 to the year 2017. The regression analysis is employed to investigate whether the five variables construct will have a relationship with the determinants of household debts in Malaysia.